2014
DOI: 10.1111/lang.12078
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Antonym Knowledge in American Sign Language (ASL) and Its Relationship to Reading Comprehension in English

Abstract: It is unknown if the developmental path of antonym knowledge in deaf children increases continuously with age and correlates with reading comprehension, as it does in hearing children. In the current study we tested 564 students aged 4–18 on a receptive multiple‐choice American Sign Language (ASL) antonym test. A subgroup of 138 students aged 7–18 took the Stanford Achievement Test reading comprehension test. The results showed that antonym knowledge depended more strongly on age for deaf children with deaf pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
4
23
0
2
Order By: Relevance
“…Siegel and Ryan (), for example, found that children with learning disabilities performed significantly more poorly than typically developing children on grammatical error correction tasks. The current results add to the growing literature of identifying language difficulties in children using signed language: BSL (Herman, Rowley, Mason, & Morgan, ; Marshall et al., ; Mason et al., ; Morgan, Herman, & Woll, ; Woll & Morgan, ) and ASL (Novogrodsky, Fish et al., ; Quinto‐Pozos et al., , Quinto‐Pozos, Forber‐Pratt, & Singleton, ). These findings suggest that reliable assessment tools may need to be developed for specific language backgrounds, such that nonnative signers’ scores should be compared to nonnative norms and native signers’ scores should be compared to native norms (Herman, Holmes, & Woll, ; Mann & Marshall, ).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Siegel and Ryan (), for example, found that children with learning disabilities performed significantly more poorly than typically developing children on grammatical error correction tasks. The current results add to the growing literature of identifying language difficulties in children using signed language: BSL (Herman, Rowley, Mason, & Morgan, ; Marshall et al., ; Mason et al., ; Morgan, Herman, & Woll, ; Woll & Morgan, ) and ASL (Novogrodsky, Fish et al., ; Quinto‐Pozos et al., , Quinto‐Pozos, Forber‐Pratt, & Singleton, ). These findings suggest that reliable assessment tools may need to be developed for specific language backgrounds, such that nonnative signers’ scores should be compared to nonnative norms and native signers’ scores should be compared to native norms (Herman, Holmes, & Woll, ; Mann & Marshall, ).…”
Section: Discussionsupporting
confidence: 57%
“…Novogrodsky, Fish et al. () further demonstrated that deaf signing children make the same kinds of developmental errors as similarly aged hearing children. Younger signing deaf children made more phonological errors on a test of ASL synonyms than did older children.…”
Section: Background Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…Critical to this discussion is the fact that knowing a language fluently is a major factor in learning about the world and crucial for success in an academic environment. Additionally, for Deaf children, research supports the notion that fluency in a first language (e.g., ASL) supports learning a second language (Novogrodsky et al, 2014a). In fact, several studies have found that ASL knowledge support the development of English literacy skills (Lange et al, 2013; Andrew et al, 2014; Ausbrooks et al, 2014; Hrastinski and Wilbur, 2016).…”
Section: Introductionmentioning
confidence: 73%